The Relationship Between Family Support and Chemotherapy Adherence in Colorectal Cancer Patients at The Digestive Surgery Clinic of Dr. Saiful Anwar General Hospital, East Java Province - Andi Surya Kurniawan; Ulan Mardani (STIKES Adi Husada, 2026)
Colorectal cancer is a malignancy with high morbidity and mortality rates, requiring chemotherapy as a major treatment modality. The effectiveness of chemotherapy is strongly influenced by patient adherence, which remains a major challenge due to physical, psychological, and social burdens. This study aimed to determine the relationship between family support and chemotherapy adherence among colorectal cancer patients. This study employed a quantitative analytic correlational design with a cross-sectional approach. The number of samples was 56 respondents. Data were collected using validated questionnaires and data analysis was performed using the Chi-Square test. The findings showed that most respondents received good family support (55.4%) and were adherent to chemotherapy (71.4%). The Chi-Square test revealed a value of χ² = 21.897 with a significance of p < 0.001, indicating a significant relationship between family support and chemotherapy adherence in colorectal cancer patients. Family support plays an essential role in improving adherence of colorectal cancer patients undergoing chemotherapy at the digestive surgery clinic of Dr. Saiful Anwar General Hospital. The better the family support, the higher the adherence level. The findings demonstrate that family support is a significant determinant of chemotherapy adherence among colorectal cancer patients. Adequate family support may help patients overcome physical discomfort, psychological distress, and treatment-related challenges, thereby promoting consistent adherence to chemotherapy schedules. These results underscore the need for healthcare professionals to integrate family involvement into patient care strategies, as strengthening family support systems may represent an effective approach to improving adherence and enhancing treatment success in colorectal cancer management.